Increased Growth and Production of Shallots (Allium ascalonicum L.) with Mulching Type treatment and Tuber Weight - Purba, Tioner; Sihaloho, Arvita; Situmeang, Ringkop; Sitinjak, Wahyunita; Sinaga, Asmina Herawaty (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the effect of mulch type and bulb weight on the growth and yield of onion production (Allium ascalonicum L.). In detail, this study aims to (1). Know the type of mulch that is most suitable for the growth and production of onion plants. (2). Knowing the weight of bulbs is best for the growth and production of onion plants. (3). Know the interaction between the type of mulch and the weight of bulbs used for the growth and production of onion plants. This study used Group Randomized Design (RAK) with 2 treatments, namely Factor I: three types of Mulch use (M): M0 = No Mulch; M1= Silver black plastic mulch (0.35 cm thick); M2= Mulch rice straw (1.5 cm thick). Factor II: three tuber weight intervals, namely: B0= 0 - 1.4 g (Small Tuber); B1= 1.5 – 1.8 g (Medium Tuber); B2 = > 1.8 g (Large Tubers). The results showed that the treatment of several types of mulch had a significant effect on plant height, weight of fresh tubers per clump, number of fresh tubers per clump, weight of fresh tubers per plot and number of fresh tubers per plot. M1 silver black plastic mulch treatment resulted in the highest plant height. weight of fresh tubers per clump (148.22 g), number of fresh tubers per clump, weight of fresh tubers per plot. Tuber weight treatment has a noticeable effect on plant height, number of leaves, weight of fresh tubers per clump, number of fresh tubers per clump, weight of fresh tubers per plot and number of fresh tubers per plot. B2 treatment yields the highest crop, number of leaves), weight of fresh tubers per clump, number of fresh tubers per clump, weight of fresh tubers per plot. The interaction of the use of several types of mulch and various tuber weights has a noticeable effect on plant height, number of leaves, weight of fresh tubers per clump, number of fresh tubers per clump, weight of fresh tubers per plot and number of fresh tubers per plot.